Why Malay elderly female frequently engaged in religious activities during leisure?: a qualitative approach in Selangor - Minhat, Halimatus Sakdiah (Malaysian Public Health Specialist Association, 2014)
Diversified leisure involvement pose various health benefits to the elderly population. However, some elderly are too focus on doing a particular type of activity during their leisure time such as religious activity. This study aims to explore factors that could possibly contribute to the higher involvement in religious activity among the Malay ethnic elderly in Malaysia. In depth interviews were conducted, involving a total of 20 elderly aged 60 years and above with stratification by background characteristics. Each interview was conducted for an average of 15 to 30 minutes. They were purposively selected from two health clinics located in two different districts in the state of Selangor, representing an urban and a rural area. Majority of the elderly interviewed perceived that by engaging in religious activities such as prayer and reciting the Holy Quran or old Islamic scripture gives them serenity or calmness. Additionally, they also felt that involvement in such activities is very synonymous with being old and therefore one should be actively involved in religious activities with increasing age. In view of the lack of diversity of leisure involvement among the elderly and the passive and solitary nature of some of the religious activities, the elderly should be made aware of the importance of participating in other types of leisure activities especially physical activities. Although, they gain spiritual and social benefits from involving in religious activities, they also need to perform other form of activities that can improve the physical health status.